Fabrication and performance of a high resolution ultra-short period W/B4C multilayer structure. (29th February 2016) - Pradhan, P C; Gangir, D; Majhi, A; Nayak, M; Biswas, A; Bhattacharyya, D; Lodha, G S
Abstract: Microstructure limited reflectivity of sputter deposited ultra-short period W/B4 C multilayers (MLs) has been studied using x-ray reflectivity, diffuse scattering and transmission electron microscopy (TEM). In order to understand the W-B4 C interface in the near-discontinuous range, the thickness of the constituent layers was systematically varied between 0.5 nm and 2.5 nm. Good density contrast and minimal thickness error were observed in MLs with individual layer thickness higher than ~1.1 nm. However, below 1.1 nm one enters into a regime where the individual layers become discontinuous, leading to embedded growth of the two constituent layers. Consequently, a significant loss of x-ray contrast was observed. In addition, increased area of contact between W and B4 C enhances the fraction of tungsten compound resulting in a layer thickness error. Based on these findings, large repetition (upto 400 bilayers) MLs with ultra-short period (down to 1.6 nm) were optimized to achieve reflectivity as high as 53% and resolving power of 149, at 8.047 keV.